FRAUD TRIANGLE DAN KORUPSI DI INDONESIA - Siregar, Anitaria (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2020)
With the corruption condition in Indonesia and the result of the research related to white-collar crime, the researcher sees this is as the room to research the fraud triangle elements which cause or as the trigger for the corruption will have occurred. Schuchter and Levi in their research conclude that only with one element of the fraud triangle, opportunity, fraud can happen. But according to the fraud triangle theory and many research, the combination of pressure, opportunity, and rationalization cause fraud. So this research will find out whether only with one element the corruption will have occurred in Indonesia or the three elements must exist. The result if this research shows only one element, opportunity, the corruption in Indonesia has happened. This result is the same as the research done by Schuchter and Levi (2015) for Swiss and Austrian elite fraudsters.